Perencanaan Drainase Air Kotor pada Pekerjaan Penataan Kawasan Bendungan Paya Seunara Kota Sabang - Gani, Fauzi A.; Irham, Irham (Portal: Jurnal Teknik Sipil, 2024)
Paya Seunara Dam is one of the water sources to meet the raw water needs of Sabang City. Around the location there are public facilities from PDAM Sabang City, as the provider of drinking water for Sabang City. The Paya Seunara Dam has a flooded area of 98.00 ha and is prepared to accommodate water with an effective capacity of 934,024 m³. The current condition of the dam is that the drainage of dirty water (wastewater drainage) of residents around the dam is carried out by directly disposing of household waste into the dam. This can result in reduced water quality in the dam. It is not allowed to dispose of wastewater from bathing, washing and kitchens of residents around the Paya Seunara Dam in Sabang City into the dam without prior wastewater treatment. It is recommended to use a mixed system septic tank with an outlet to the infiltration field for the number of bathing, washing and kitchen wastewater producers of more than 10 people in locations with low groundwater (SNI 2398:2017). The capacity of the septic tank and infiltration field described in this technical justification is for 50 people. The calculation was carried out using the SNI 2398:2017 method. From the design results, two septic tanks and infiltration fields were obtained for a capacity of 50 people each. The dimensions of the septic tank obtained from the calculation results are 3.8 m long, 2.7 m wide, and 1.939 m high.